Silent scars: understanding interpersonal sensitivity, paranoid ideation, and hostility from adverse childhood experiences in Jamaica - Johnson, Rosemarie; Galbraith, Elroy; Gibson, Roger Carl; Coley, Tracey-Ann (Frontiers in Psychology, 2025)
BackgroundAdverse childhood experiences (ACEs) are known to predict adverse outcomes related to physical and mental health, including anxiety and depression. How ACEs predict the outcomes of interpersonal sensitivity, paranoid ideation, and hostility, which are known to be associated with impaired interpersonal relationships, interpersonal conflict and violence, is less well researched. Consequently, this study aimed to determine the extent to which the number and types of ACEs that individuals experienced were associated with these outcomes, and whether these relationships were moderated by the sociodemographic variables of age, sex, educational level, and relationship status.MethodThe study used data from a survey of 1,633 adult Jamaicans who constituted a non-probability sample. They were recruited via flyers that were placed on social media, at doctor's offices, in supermarkets, at places of work, and at educational institutions. The survey consisted of sociodemographic items, as well as the Adverse Childhood Experiences International Questionnaire (ACE-IQ) and the Symptom Checklist-90-Revised (SCL-90-R). A correlational design, using Pearson's correlation analyses, was used to assess the association between overall past ACEs and specific current interpersonal psychopathological vulnerabilities, namely interpersonal sensitivity, paranoid ideation, and hostility. Regression analyses were also used to determine which specific childhood adversities were associated with these vulnerabilities.ResultsMost participants (70.5%) reported having experienced at least four of the 13 categories of ACEs explored in the ACE-IQ. There were positive correlations among the ACE-IQ and SCL-90-R subscales of interest (interpersonal sensitivity, paranoid ideation, and hostility), with correlation coefficients ranging from 0.249 to 0.770 (p < 0.001). Emotional abuse was the most commonly reported ACE (70.5%), followed by violence in the home (69.3%), and community violence (66.9%). Seven of the 13 ACEs from the ACE-IQ were associated with all three mental health outcomes. Physical abuse had an inverse relationship with paranoid ideation, as did household alcohol or drug misuse with interpersonal sensitivity and hostility. The relationships between ACEs and the interpersonal psychopathological vulnerabilities were not moderated by the sociodemographic variables.ConclusionsThe number of ACEs (ACE-IQ score) was positively correlated with all three psychopathological outcomes. Many ACEs were associated with one or more of these outcomes. A few ACES exhibited an inverse relationship with either paranoid ideation or hostility and interpersonal sensitivity. These findings add new knowledge to an under-explored area and are discussed in relation to prior research, theory, and practice.